Corporate social responsibility and management in a glocal context - Silva, Maria (2021)
Corporate social responsibility (CSR) has become a recurrent and global concept used by international and local corporations, with its supporters, skeptics, and critics. It is also a growing area of concern and practice for businesses for answering the challenges of the present century, such as fighting poverty or promoting sustainable development goals. There is need—almost consensual—for clarifying the impact and the policy setting related to complex areas, such as climate change, environmental issues, social responsibility and a whole array of ethical issues, at global and at the local level (i.e., through an unavoidable glocal perspective). The purpose of this chapter is, first, to review the literature and the main issues related to corporate social responsibility; second, to identify the current challenges this scientific area is facing; and, third, to pinpoint its relevance at the level of the digital economy setting, for the management of the emergent business models and of the information systems management of businesses.